On the kinematic of a 3-DOF Stewart platform - Bürüncük, K; Tokad, Y (John Wiley & Sons Inc, 1999)
The kinematic behavior of the Stewart platform has been discussed in the literature by many researchers. In the present article, a special form of the Stewart platform, namely, the 3-degrees of freedom platform with triangular shaped base and upper platforms, is considered by thoroughly deriving a new set of constraint equations which makes it possible to discover several new properties of the platform. Both the inverse and direct kinematic problems are discussed and a new approach for solution of the direct kinematic problem is described which gives all the real (physical) solutions. (C) 1999 John Wiley & Sons, Inc.
Keywords: Parallel Manipulators